The human genome - Heos, Bridget. 4 0 16; 5 (New York : Rosen Publishing, 2011)
An exploration of the human genome that discusses what it consists of and examines how it is mapped.
The basics of the human genome -- The history of genetics and the human genome project -- The chromosomes -- Human heredity -- Human history -- Genetic diseases -- Ethics and the genome -- The future.
Includes bibliographical references (p. 73-77) and index.
7.7;Young Adult;Young Adult.
Keywords: 2 -- 0; 6; Human genome;Genetics -- 20 -- Juvenile literature.;Juvenile literature; 20; 2